Answer:
C.0, 500
Step-by-step explanation:
Answer:
- incorrect
- correct
- incorrect
Step-by-step explanation:
A + B = (-4x^2 +2x -5) +(3x^2 +6) = x^2(-4+3) +x(2) +(-5+6) = -x^2 +2x +1
The given sum is Incorrect.
__
A - C = (-4x^2 +2x -5) -(-5x -4) = -4x^2 +x(2+5) +(-5+4) = -4x^2 +7x -1
The given difference is Correct.
__
B + C = (3x^2 +6) +(-5x -4) = 3x^2 -6x +2
The given sum is Incorrect.
5(a + 3b) = 5(9 + 3(2)) = 5(9 + 6) = 5(15) = 75
Answer:
2x^2+x+6
Step-by-step explanation:
if the 4x3 meant 4x^3, then im pretty sure this is the correct answer